The feasibility and acceptability of clean fuel use among rural households. A pilot study in Central Ghana - Theresa Tawiah; Seidu Iddrisu; Stephanie Gyaase; Mieks Twumasi; Kwaku Poku Asante; Darby Jack (Journal of Public Health in Africa, 2022)
Background: 76% of the population in Ghana uses solid fuels as their primary source of cooking energy, including 41.3% firewood and 31.5% charcoal. Consequently, household air pollution (HAP) continues to be the leading risk factor for the majority of illness burden in the country. In the past, aggressive LPG distribution and adoption schemes have been implemented to reduce HAP in Ghana. Nevertheless, just 22% of Ghanaian households utilize LPG for cooking.